2019
DOI: 10.1002/jcb.29459
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐3691‐5p is upregulated in docosahexaenoic acid‐treated vascular endothelial cell and targets serpin family E member 1

Abstract: Endothelium, the inner cellular lining of blood vessels, has an important role in the regulation of physiological processes and its dysfunction may initiate cardiovascular complications. Previous investigations have revealed that dietary docosahexaenoic acid (DHA) is related to a lower possibility of cardiovascular disease and mortality. Until now, the molecular mechanisms in the biological activities of DHA remain largely unknown. MicroRNAs (miRNAs) play a vital role in regulating gene expression. Thus, we ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“… 62 In human umbilical vein endothelial cells, docosahexaenoic acid, which is known to be a healthy dietary factor, induced miR-3691-5p to post-transcriptionally silence SERPINE1. 63 In the setting of hepatopulmonary syndrome, PAI-1 in pulmonary microvascular endothelial cells is a direct target of miR-145-5p. 64 A separate study on human pulmonary microvascular endothelial cells reported on targeting of PAI-1 by miR-30c and miR-301a.…”
Section: Discussionmentioning
confidence: 99%
“… 62 In human umbilical vein endothelial cells, docosahexaenoic acid, which is known to be a healthy dietary factor, induced miR-3691-5p to post-transcriptionally silence SERPINE1. 63 In the setting of hepatopulmonary syndrome, PAI-1 in pulmonary microvascular endothelial cells is a direct target of miR-145-5p. 64 A separate study on human pulmonary microvascular endothelial cells reported on targeting of PAI-1 by miR-30c and miR-301a.…”
Section: Discussionmentioning
confidence: 99%